Factors That Contribute To The Percentage Of Body Fat Among Malaysian Adolescents - Ang, Merlin (2003)
Obesity or excess body fat in adolescents has become an increasing clinical and public health concern worldwide. In adolescents, body fat accumulation is a complex interaction of dietary, physical activity, genetic, environment and social factor. This study aims to determine the factors that contribute to the percentage of body fat among Malaysian adolescents. A non-experimental cross sectional study was carried out among Form One and Two secondary students (11 to 15 years old) in Kedah and Pulau Pinang. Respondents were selected from a three-staged stratified random sampling from schools that fulfilled the inclusion criteria of co-educational, multiracial composition, nonreligious and non-residential. Of the 6555 respondents (screening), the prevalence of underweight, normal weight and overweight was 11.3%, 70.9% and 17.7% respectively. While underweight prevalence was higher among the rural adolescents, prevalence of overweight was higher among the urban adolescents. Body Mass Index measurements (n = 769) was found to be a good measure of percentage of body fat (sensitivity and specificity).